SUPERVISI MANAJEMEN LAYANAN KANTIN SEHAT DI SEKOLAH ADIWIYATA (STUDI KASUS DI SMPN 3 SAMPANG DAN SMPN 1 KETAPANG KAB. SAMPANG) - Solikin Solikin (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The purpose of this study is to describe the background, planning, implementation, supervision, and impact of healthy canteen services in SMPN 3 Sampang and SMPN 1 Ketapang. This research uses a qualitative approach, with a case study research design. From the results of the study it was found that: (1) The background of holding a healthy canteen service at the school was due to concern over the number of snacks that are not healthy and not environmentally friendly; (2) The planning for healthy canteen services includes the division of tasks of teachers appointed as coordinators and implementing members of healthy canteens, making MoUs between schools and food sellers, planning the construction of healthy canteens and procuring supporting infrastructure and the determination of the budget to be used; (3) The implementation of healthy canteen services includes activities to provide healthy food and drinks and to provide canteen facilities and infrastructure in accordance with health and environmentally friendly standards; (4) Supervision of healthy canteen services includes internal and external supervision; and (5) The impact of healthy canteen services at the school is the fulfillment of the need to obtain hygienic and nutritious food and drink at school, building the character of students to be able to choose healthy food, the realization of a clean, healthy and comfortable and environmentally friendly school environment.